The efficacy and safety of the biosimilar product (Inflectra®) compared to the reference drug (Remicade®) in rescue therapy in adult patients with ulcerative colitis - Magdalena Kaniewska; Andrzej Moniuszko; Grażyna Rydzewska (Gastroenterology Review)
Introduction : The biosimilar product Inflectra® has been approved by the European Medicine Agency (EMA) for the same indications as its reference drug, infliximab, based on studies in patients with rheumatic diseases. Thus far, there have not been enough data regarding its efficacy and safety in ulcerative colitis (UC). Aim : To assess the efficacy and safety of the biosimilar product Inflectra® in comparison with its reference biological agent (Remicade®) in rescue therapy in adult patients presenting with severe exacerbation of UC, as well as to evaluate recurrence rate during a 6-month observation after finish of treatment. Material and methods : In a single-centre retrospective study, a cohort of 83 adult patients with severe UC treated at the Department of Gastroenterology with Inflammatory Bowel Diseases Subdivision of the Central Clinical Hospital of MSWiA, Warsaw was investigated. All patients received three induction doses of Remicade® (28 individuals) or Inflectra® (55 individuals) based on the same criteria of the National Health Fund (NFZ) Therapeutic Program (total Mayo score > 6). Activity of the disease was evaluated on the Mayo scale at qualification, after finishing the rescue treatment (after 14 weeks), and after a 6-month observation period. In all patients, sigmoidoscopy was performed at qualification and after induction (after three doses). Results : The studied groups were similar with respect to age and sex distribution, duration of the disease, extent of the disease (left-sided type, pancolitis), additional pharmacotherapy, and smoking. Clinical response following three induction doses was noted in 81% of patients receiving Remicade® compared to 77% receiving the biosimilar product, Inflectra® (NS); while clinical remission was observed in 42% receiving Remicade® and 32% receiving Inflectra® (NS), respectively. Endoscopic remission assessed as 0 on the Mayo scale was achieved in 4 (15%) patients on Remicade® and in 7 (13%) patients on Inflectra® (p = 0.45). Relapse occurred in 68% of all patients, while 51% presented with exacerbation of the disease 3 months after finishing biological treatment. In 93%, exacerbation occurred within 12 months. The recurrence rate was similar in both groups (75% with Remicade®, 64% with Inflectra®, respectively). Side effects occurred with similar frequency in both groups. Conclusions : In the study, it was established that the biosimilar drug (Inflectra®) has a similar efficacy and safety as the reference biological agent (Remicade®), not only in rescue therapy, but also during a 6-month observation period in adult patients with severe UC. Low mucosal healing rate in both groups and high recurrence rate of the disease soon after finishing induction treatment indicate the need for prolonged therapy with infliximab in patients with severe UC.